Ex vivo expansion of haematopoietic stem/progenitor cells from human umbilical cord blood on acellular scaffolds prepared from MS‐5 stromal cell line. (17th April 2012) - Tiwari, Abhilasha; Tursky, Melinda L.; Mushahary, Dolly; Wasnik, Samiksha; Collier, Fiona M.; Suma, Kantipudi; Kirkland, Mark A.; Pande, Gopal
Abstract: Lineage‐specific expansion of haematopoietic stem/progenitor cells (HSPCs) from human umbilical cord blood (UCB) is desirable because of their several applications in translational medicine, e.g. treatment of cancer, bone marrow failure and immunodeficiencies. The current methods for HSPC expansion use either cellular feeder layers and/or soluble growth factors and selected matrix components coated on different surfaces. The use of cell‐free extracellular matrices from bone marrow cells for this purpose has not previously been reported. We have prepared insoluble, cell‐free matrices from a murine bone marrow stromal cell line (MS‐5) grown under four different conditions, i.e. in presence or absence of osteogenic medium, each incubated under 5% and 20% O2 tensions. These acellular matrices were used as biological scaffolds for the lineage‐specific expansion of magnetically sorted CD34 + cells and the results were evaluated by flow cytometry and colony‐forming assays. We could get up to 80‐fold expansion of some HSPCs on one of the matrices and our results indicated that oxygen tension played a significant role in determining the expansion capacity of the matrices. A comparative proteomic analysis of the matrices indicated differential expression of proteins, such as aldehyde dehydrogenase and gelsolin, which have previously been identified as playing a role in HSPC maintenance and expansion. Our approach may be of value in identifying factors relevant to tissue engineering‐based ex vivo HSPC expansion, and it may also provide insights into the constitution of the niche in which these cells reside in the bone marrow. Copyright © 2012 John Wiley & Sons, Ltd.